ENFORCEMENT OF THE ITE LAW AND THE IMPACT OF ONLINE GAMBLING PROMOTION BY INFLUENCERS ON THE YOUTH IN TOMOHON: Penegakkan Hukum ITE dan Dampak Promosi Judi Online oleh Selebgram terhadap Generasi Muda di Tomohon - Nopesius Bawembang; Joice Umboh; Herts Taunaumang; Christiane Aprilia Paendong; Johanis Lukas Siegfrid Sebril Polii (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
Online gambling's explosive expansion and the widespread reach of social media platforms have raised serious concerns, especially with regard to its effects on young people. This study investigates how young people in Tomohon, Indonesia, perceive and behave in response to online gambling ads via Instagram influencers (selebgram). The goal of this study was to find out how young people's attitudes and comprehension of the legal ramifications of online gambling are influenced by their exposure to gambling advertisements on social media. Twenty young people between the ages of 18 and 25 participated in in-depth interviews and focus groups as part of a qualitative research approach, which also included a content analysis of Instagram posts endorsing online gambling. According to the study, a sizable percentage of participants (75%) had encountered online gambling ads, and 60% said they would like to try it out despite their lack of knowledge about the potential legal repercussions. Furthermore, it was discovered that young people's views of online gambling as an enjoyable and possibly lucrative pastime were influenced by their frequent usage of social media and the favorable representation of gambling by influencers. The study comes to the conclusion that in order to inform young people about the dangers and potential legal repercussions of online gambling, there is an urgent need for more legal literacy and focused awareness initiatives. Furthermore, to stop the marketing of online gambling on social media platforms, stricter regulations are needed.